Analisis Pola Kemitraan Petani Tebu (Saccharum officinarum Linn) di PT. PG Rajawali II Unit PG Subang - Budi, Noman; Yusiana, Ekalia; Budiandrian, Bayu (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
PG Rajawali II unit of PG Subang made a partnership program as a solution to the company's crisis as well as a form of integrated agriculture implementation. After approximately 5 years of running the partnership program, there are still things that are felt to be lacking from this partnership program, such as capital, facilities and infrastructure, guarantee of selling prices for partner farmers, and lack of attention from the factory that is evenly distributed to all partner farmers. This study aims to see the results related to the PG Subang partnership program in the context of partnership patterns and farmer satisfaction. This study uses a descriptive quantitative approach and is supported by descriptive qualitative data. The researcher assigned 80 partner farmers as respondents using simple random sampling, a measurement tool using a Likert scale. Overall, PG Subang's partnership program is in the good category. The partnership pattern used by PG Subang is the Plasma Core partnership pattern, in this case PG Subang moves as the core and partner farmers as plasma. With an importance value of 4.89, there are aspects of reliability and responsiveness that show that farmers are very concerned about the stability and availability of support from the program. However, there is still concern about the PG's response. Subang in responding to complaints and solving problems in the field.